The Prevalence of Overemployment in Penang: A Preliminary Analysis - Fernandez, Jacqueline Liza; Ee, Shiang Lim (Universiti Sains Malaysia, 2016)
Nowadays, workers tend to face the problem of overemployment where desired working hours are less than their actual working hours. Some overemployed workers desire to work less hours although there may be a concomitant decline in earnings. This research is conducted to study the factors that are related to the employment status of workers in Penang with regard to being overemployed or otherwise. This research uses primary data that was collected in a survey that was done in one particular state in Malaysia, namely Penang. The questionnaires were distributed to workers in different areas in Penang. A total of 525 respondents were surveyed in this study. This paper reports the preliminary findings of the study by presenting the bivariate relationship between the employment status of workers and various demographic, socio-economic and work-related variables. The initial findings of this study provide the basis for some general conclusions and policy implications on the issue of overemployment in Penang.